(untitled) (Acta Scientiarum. Biological Sciences, 2017)
Our objective was to group in ecotypes 12 serovars of Salmonella isolated from shrimp farming environments in the State of Ceara (Northeast Brazil). Grouping was done based on genotypic virulence factors. Two groups based on the similarity of the Box-PCR were identified: a group consisting of three strains (01 S. ser. Madelia serovar and 02 S. ser. enterica subs. houtenae) and another group consisting of nine isolates (02 S. ser. Saintpaul serovars; 03 S. ser. Infantis; 02 S. ser. Panama; 01 S. enterica subs. enterica; and 01 S. enterica subs. houtenae). Distribution pattern of the serovars was not influenced by the origin matrices (water and sediment). Plasmid virulence genes pefA and invA were detected, unrelated to the serovar and environmental origin of the isolates. The presence of virulence genes in the isolates underlines the potential to trigger salmonellosis events via shrimp consumption. Biomonitoring of these sources of contamination should be encouraged as a protective measure, minimizing health risks and economic losses for the industry.